Generalized pseudo inverse kinematics at singularities for developing five-axes CNC machine tool postprocessor - My, Chu Anh; Hai, Vuong Xuan (Vietnam Journal of Mechanics, 2013)
This paper presents an analytical scheme for analyzing the singular configuration problem of general five-axes CNC machine tool. A computational technique based on the generalized pseudo inverse kinematics for finding out feasible solution of the problem is proposed. The technique is then used for developing post processor algorithm of five-axes CNC machine tool. Typical examples of singularity analysis are carried out, and real cutting parts are implemented for verifying the research result.